## 矩陣運算的基本技巧

$A(A+B)^{-1}B=B(A+B)^{-1}A$

1. 分配律 $A(B+C)=AB+AC$$(A+B)C=AC+BC$
2. 結合律 $A(BC)=(AB)C$
3. 矩陣乘法交換律不總是成立，但若 $A$ 是可逆的，則存在 $B$ 使得 $AB=BA=I$，交換律在此情況下成立。

$(A+B)(A+B)^{-1}=I$

$A(A+B)^{-1}=I-B(A+B)^{-1}$

\begin{aligned} A(A+B)^{-1}B-B(A+B)^{-1}A&=\left(I-B(A+B)^{-1}\right)B-B(A+B)^{-1}A\\ &=B-B(A+B)^{-1}B-B(A+B)^{-1}A\\ &=B-B(A+B)^{-1}(B+A)\\ &=B-B=0.\end{aligned}

$(A+B)A^{-1}(A-B)=(A-B)A^{-1}(A+B)$

\begin{aligned} (A+B)A^{-1}(A-B)&=(A+B)(I-A^{-1}B)\\ &=A+B-B-BA^{-1}B=A-B+AA^{-1}B-BA^{-1}B\\ &=(A-B)+(A-B)A^{-1}B=(A-B)\left(I+A^{-1}B\right)\\ &=(A-B)A^{-1}(A+B). \end{aligned}

$A(B-I)-(B-I)=(A-I)(B-I)=I$

$(A^{-1}+B^{-1})^{-1}=A-A(A+B)^{-1}A$

$(A^{-1}+B^{-1})\left(A-A(A+B)^{-1}A \right)=I$

$X=I+B^{-1}A-(A+B)^{-1}A-B^{-1}A(A+B)^{-1}A$

\begin{aligned} BX&=B+A-B(A+B)^{-1}A-A(A+B)^{-1}A\\ &=B+A-(B+A)(A+B)^{-1}A\\ &=B+A-A=B.\end{aligned}

$(I-AB)^{-1}=I+A(I-BA)^{-1}B$

$(I-AB)\left(I+A(I-BA)^{-1}B\right)=I$

$(I-AB)\left(I+A(I-BA)^{-1}B\right)=I-AB+A(I-BA)^{-1}B-ABA(I-BA)^{-1}B$

\begin{aligned} A(I-BA)^{-1}B-ABA(I-BA)^{-1}B&=A(I-BA)(I-BA)^{-1}B\\ &=AB,\end{aligned}